Peran Director of Photography dalam Produksi Video Feature “Kabaret Bandung: Seni Berbicara, Bahasa Berkarya” dengan Penerapan Teknik Sinematografi - Zhilan Dzulfiqar Sailan; Santi Susanti; Teddy Kurnia Wirakusumah (BADAN PENERBIT STIEPARI PRESS, 2025)
“Kabaret: Seni Berbica, Bahasa Berkarya” is a video feature that highlights cabaret as a medium for developing language and artistic skills, particularly among students. This work focuses on the role of the Director of Photograohy (DoP) in shaping visual quality that suppots narrative and emotional element in performing arts documentation. Tehe video combines documentation of cabaret performances, rehearsals, and interview with kwy figures as the main storytelling components. The applied cinematographic concept includes visual composition , lighting, camera angle selection, and movement techniques to create a dynamic and immersive visual presentation. The purpose of this report is to explain the responsibilities and contributions of the DoP across all production. This video successful applies key principles of cinematography, resulting in a work is not only visual aesthetic but also informative and inspiring for a broader audience.